Evaluating the quality of service of the Internet of Bio-Nano Things in possible scenarios of applicability in the nanomedicine - Nieto Chaupis, Huber (2017)
Once the Internet of Bio-Nano Things (IoBNT) is already running, one important aspect that must be established is the estimation of parameters of the quality of service (QoS). From the view of the end-user, QoS should be high enough in order to guarantee an excellent applicability of the IoBNT, in particular when humans are part of the network and where efficient techniques of nanomedicine are foresen. In this paper, we present a scheme where the QoS is calculated when the IoBNT is applied for sensing abnormalities in kidney. For this end the following key points are considered: (i) sensing of charged proteins through THz waves, (ii) reception by bio-cyber device and subsequent emission of MHz waves, (iii) reception by smartphone, (iv) reception and storing of information at the cloud, (v) exchanging information with server and world-wide-web, and (vi) final reception and treatment of data by the enduser. The estimation of the full QoS has paid attention to the atomic absorption of THz waves by water in human tissue, fact which might degrade the optimal surveillance of the sensing of proteins and which is translated as the main source of errors. The full nonlinear expression is numerically evaluated by obtaining in average a QoS of order of 90±8%.